2011
DOI: 10.1002/bsl.965
|View full text |Cite
|
Sign up to set email alerts
|

Exploring separable components of institutional confidence

Abstract: Despite its contemporary and theoretical importance in numerous social scientific disciplines, institutional confidence research is limited by a lack of consensus regarding the distinctions and relationships among related constructs (e.g., trust, confidence, legitimacy, distrust, etc.). This study examined four confidence-related constructs that have been used in studies of trust/confidence in the courts: dispositional trust, trust in institutions, obligation to obey the law, and cynicism. First, the separabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
(35 reference statements)
1
22
1
Order By: Relevance
“…Items used in our studies were adapted from or inspired by the listed sources, not used verbatim. Many of the items were also used in prior studies (Hamm, PytlikZillig, Herian, Bornstein, et al, 2013;Hamm et al, 2011). .050* 34025.3** 34452.1** Table 1 for model definitions.…”
Section: Unspecified Trustmentioning
confidence: 99%
“…Items used in our studies were adapted from or inspired by the listed sources, not used verbatim. Many of the items were also used in prior studies (Hamm, PytlikZillig, Herian, Bornstein, et al, 2013;Hamm et al, 2011). .050* 34025.3** 34452.1** Table 1 for model definitions.…”
Section: Unspecified Trustmentioning
confidence: 99%
“…Although somewhat beyond the scope of the article and not reported here because of concerns with sample size, an additional structural equation model with these data regressed both CLI subscale latent factors on scale scores of Trust in Governmental Institutions, Dispositional Trust, Cynicism, and Obligation to Obey and revealed that although Dispositional Trust was also predictive for the police, the only significant predictor of CLI-Courts subscale was Cynicism. When considered in light of other work in the courts context with similar measures (Hamm et al, 2013;Hamm et al, 2011), the current results suggest an especially important role for cynicism for older adults. In the previous work with more general samples, Cynicism was often predictive but always eclipsed in effect size by either Dispositional Trust or Trust in Governmental Institutions.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, of the research that has addressed these measurement shortcomings (Hamm et al, 2013;Hamm et al, 2011), most has been somewhat limited in its ability to generalize to specific legally relevant subpopulations because of its use of student or general community samples. Thus, it remains somewhat unclear how well existing multi-item measures of confidence perform in specific, criminal justice-relevant subpopulations like older adults.…”
mentioning
confidence: 99%
“…In order to shed further light on the separability and explanatory power of confidencerelated constructs as predictors of different operationalizations of confidence in the courts, we examined the dimensionality and predictive ability of four trust-related constructs (dispositional trust, trust in institutions, obligation to obey the law, and cynicism toward the law) on confidence in the courts measured either as unspecified confidence, perceived trustworthiness, or specific expectations of the courts (Hamm et al, 2011). The predictor constructs were chosen because they were both important theoretically relevant trust-related constructs in the literature, and because they varied on the potentially important dimensions of globality (dispositional trust is very global, trust in government is more specific, specific expectations are even more specific), valence (cynicism is negatively valenced while trust in government is positively valenced), and expectational focus (e.g., assessing expectations of one's self to obey the law versus specific expectations of the institution).…”
Section: Deconstructing Confidencementioning
confidence: 99%
“…Significantly, however, the importance of these four constructs varied across studies and operationalizations of confidence (we treat this further in the discussion). Hamm et al (2011), table 7: study 2 item total regressions. Note: T1 = Time 1, T2 = Tme 2.…”
Section: Deconstructing Confidencementioning
confidence: 99%